PENGARUH MOTIVASI INTERNAL, EKSTERNAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN UNIVERSITAS PASIR PENGARAIAN - ’Aini, Yulfita (E-Journal Cano Ekonomos, 2013)
The aim of this research is to analyze impacts of internal motivation, external motivation and work environment on the employees performance at Universitas Pasir Pengaraian. 35 people used as responden in this research. The results based on multiple regression method shown that internal motivation, external motivation and work environment simultaneously significantly impact employee performance, with 58,7 % R2 value. The results from the partial test, shown that external motivation and work environment significantly impact employee performance, but internal motivation does not significantly impact employee performance. External motivation has the dominant impact on employee performance. With 48,5% r2 value.